The World of open and distance learning - Venugopal Reddy, V.; Manjulika, S. (New Delhi : Viva Books, 2000)
Contributed case studies with reference to developing countries.
Includes bibliographical references and index.
BIED
Keywords: Distance education; Open learning -- Social science